Prospects of soil microbiome application for lignocellulosic biomass degradation: An overview - Singh R.; Pal D.B.; Alkhanani M.F.; Almalki A.H.; Areeshi M.Y.; Haque S.; Srivastava N. (My University, 2025)
Sustainable and practically viable biofuels production technology using lignocellulosic biomass is still seeking its way of implementation owing to some major issues involved therein. Unavailability of efficient microbial sources for the degradation of cellulosic biomass is one of the major roadblocks in biomass to biofuels production technology. In this context, utilization of microbiomes to degrade lignocellulaosic biomass is emerging as a rapid and effective approach that can fulfill the requirements of biomass based biofuels production technology. Therefore, the present review is targeted to explore soil metagenomic approach to improve the lignocellulosic biomass degradation processing for the cost-effective and eco-friendly application. Soil microbiomes consist of rich microbial community along with high probability of cellulolytic microbes, and can be identified by culture independent metagenomics method which can be structurally and functionally explored via genomic library. Therefore, in depth analysis and discussion have also been made via structural & functional metagenomics tools along with their contribution to genomic library. Additionally, the present review highlights currently existing bottlenecks along with their feasible solutions. This review will help to understand the basic research as well as industrial concept for the process improvement based on soil microbiome mediated lignocellulosic biomass degradation, and this may likely to implement for the low-cost commercial biofuels production technology. © 2022